Fungal diseases of economically important tree species in plantation forest of Arjam, Myagdi district, Nepal - Jha, Sanjay Kumar; Shrestha, Shashi (Banko Janakari, 2022)
This paper deals with the fungal diseases of important tree species, which have enormous economic value, i.e. Melia azedarach, Celtis australis and Toona ciliata. These tree species are used for timber, fuelwood, fodder and for infrastructure development. A number of devastating fungal diseases were prevalent among the tree species in plantation forest of Myagdi District. For Isolation and identification of pathogen infected samples were cut into small pieces, washed, sterilized with 70% ethanol and transferred to Petri plates containing potato dextrose agar (PDA) media. Then, incubated at 25 ± 2ºC and after few days when fungal colonies developed observed in microscope. These fungal pathogen causing different disease were Erysiphe kusanoi (powdery mildew), Colletotrichum gloeosporioides (anthracnose), Pestalotia neglecta and Fusarium sp. (canker) and Alternaria alternata (blight). It has been concluded that to moderate the damages caused by these pathogens, it is must to identify them early in the infection process.